The lives of great Christians - Cook, William R. (William Robert), 1943-; Teaching Company (Chantilly, Va : Teaching Co., 2007)
Historian William Cook discusses the lives of prominent Christians through the ages.
pt. 1. disc 1. lectures 1-6. Introduction : what makes a great Christian? ; Paul and the first Christian missionaries ; The early martyrs ; St. Antony, the first monk ; The desert fathers and mothers ; Augustine -- pt. 1. disc 2. lectures 7-2. St. Patrick and the conversion of Ireland ; St. Benedict and his rule ; Leo IX, Gregory VII, and church reform ; Bernard of Clairvaux and Monastic reform ; Francis of Assisi ; Clare of Assisi -- pt. 2. disc 3. lectures 13-18. Catherine of Siena ; Bernardino of Siena ; John Hus and the Hussites ; Thomas More ; Martin Luther ; John Wesley and the origins of Methodism -- pt. 2. disc 4. lectures 19-24. The monks of Mount Athos ; Dietrich Bonhoeffer and Maximilian Kolbe ; Damien of Molokai and Teresa of Calcutta ; From slavery to Martin Luther King ; Gustavo Gutierrez and liberation theology ; Defining the Christian life.
DVD, region 1.
"Course no. 6481."
In two containers ; title from containers.
Accompanying guide includes biographical information, lecture notes and outlines, timelines, glossaries, and bibliographical references.
Lecturer, William Cook, State University of New York at Geneseo.
Twenty-four lectures (30 min each) on four discs, two discs in each container.
Keywords: Christian biography; Church history; Christian saints -- Biography